2017
DOI: 10.1039/c6ta09424d
|View full text |Cite
|
Sign up to set email alerts
|

Hollow carbon spheres and a hollow carbon sphere/polyvinylpyrrolidone composite as ammonia sensors

Abstract: Hollow carbon sphere sensors were used to determine NH3 in a humid environment using a tristimulus pattern recognition approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 93 publications
(94 reference statements)
2
34
1
Order By: Relevance
“…[17] Second, there is electron transfer from the polymer matrix to CNTs as revealed by the band alignment between CNT and PS-b-P4VP (for more details,s ee the Supporting Information, Figure S11). Furthermore,the lone pair of electrons from the exposed vapors interacts with the CNT surface and transfers electrons to CNT,f urther enhancing the conductivity of the sensor [18] implying that protonic coupled with electronic conduction is the dominant mechanism in case of CNT-PSb-P4VP sensors.T his is consistent with our observations that pristine PS-b-P4VP sensors have lower sensitivity and are significantly slower compared to CNT-PS-b-P4VP.W ea lso fabricated humidity sensors with only CNTs and found that the resistance change is minor which first decreases and then increases with humidity change (Supporting Information, Figure S12). This can be attributed to the low cross-linking of CNTs,a sr eported elsewhere.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[17] Second, there is electron transfer from the polymer matrix to CNTs as revealed by the band alignment between CNT and PS-b-P4VP (for more details,s ee the Supporting Information, Figure S11). Furthermore,the lone pair of electrons from the exposed vapors interacts with the CNT surface and transfers electrons to CNT,f urther enhancing the conductivity of the sensor [18] implying that protonic coupled with electronic conduction is the dominant mechanism in case of CNT-PSb-P4VP sensors.T his is consistent with our observations that pristine PS-b-P4VP sensors have lower sensitivity and are significantly slower compared to CNT-PS-b-P4VP.W ea lso fabricated humidity sensors with only CNTs and found that the resistance change is minor which first decreases and then increases with humidity change (Supporting Information, Figure S12). This can be attributed to the low cross-linking of CNTs,a sr eported elsewhere.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Among the carbonaceous materials, carbon nanotubes and graphene are the most employed in the electrochemical sensors and biosensors development, [37,38] while few papers report on CSs in electrochemical devices. [39][40][41][42][43][44][45] In addition, none of these papers investigated the CSs electrochemical behavior in terms of magnetic and nonmagnetic properties. For this reason, we directly evaluated the electrochemical performance of the CSs by drop casting a dispersion of CSs on electrochemical chips (E-chips) and analyzing the response toward several clinically relevant analytes.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Second, there is electron transfer from the polymer matrix to CNTs as revealed by the band alignment between CNT and PS‐ b ‐P4VP (for more details, see the Supporting Information, Figure S11). Furthermore, the lone pair of electrons from the exposed vapors interacts with the CNT surface and transfers electrons to CNT, further enhancing the conductivity of the sensor implying that protonic coupled with electronic conduction is the dominant mechanism in case of CNT‐PS‐ b ‐P4VP sensors. This is consistent with our observations that pristine PS‐ b ‐P4VP sensors have lower sensitivity and are significantly slower compared to CNT‐PS‐ b ‐P4VP.…”
Section: Figurementioning
confidence: 99%